The Effect of Health Education with Leaflet Media on Improving Knowledge and Attitude of Tb Patients at Rotinsulu Pulmonary Hospital, Bandung - Tri Ardayani; Neti Sitorus; Rudy Mulyana Muwardi (CV Media Inti Teknologi, 2025)
Background: Mycobacterium tuberculosis is the bacterium that causes tuberculosis, an infectious disease that targets the lungs, particularly the lung parenchyma.Aims: This study aims to increase the understanding and mindset of the patient's family about tuberculosis prevention therapy and other aspects of TB prevention and treatment through health education, especially by utilizing media such as leaflets.Methods: Pre-experiment design using the One Group Pre-test-Post-test research method is the type of study being conducted. There were 412 participants in this study. Using a purposive sampling technique, 30 persons made up the study's sample. A questionnaire was the tool utilized. The KEPK STIK Immanuel Bandung has recommended this study (No.132/KEPK/STIKI/XII/2021).Result: According to the study's findings, the majority of respondents had adequate understanding (80.0%) prior to receiving leaflets, and a good level of knowledge (83.3%) following leaflet distribution. The majority of respondents had a good attitude before receiving the leaflets (70.0%), and this attitude remained positive after receiving the leaflets (96.7%). Health Education Through Leaflet Media Has an Impact on TB Knowledge patients both prior to and following the operation. Health education using leaflet media has an impact on TB patients' attitudes both before and after the intervention. Conclusion: The findings indicate that health education via leaflet media has an impact on the attitudes and knowledge of patients with pulmonary tuberculosis. It is suggested that Rotinsulu Regional Hospital establish a regular health education program.